LOGISTICS SERVICE PROVIDER – 4PL MODEL PERSPECTIVES - Vivaldini, Mauro (Contextus - Contemporary Journal of Economics and Management, 2019)
Based on a theoretical approach, this research explores and analyzes logistics outsourcing, with a specific focus on the 4PL model. The intention is to know how this provider is usually understood and to present not only the main factors that characterize it but also what perspectives it has ahead. This paper, while bringing a discussion of the theme supported by theory, contributes an analysis of its role in logistics operations, as well as presents and discusses the main factors that define its activities, critical points and perspectives. The discussions presented indicate factors related to 4PL's future perspectives, while serving as a basis for several new researches, since they signal propositions regarding this model of logistic service delivery.